A human skin-on-a-chip platform for microneedling-driven skin cancer treatment - Natan R. Barros; Raehui Kang; Jinjoo Kim; Menekse Ermis; Han-Jun Kim; Mehmet R. Dokmeci; Junmin Lee (Materials Today Bio)
Skin-on-a-chip models provide physiologically relevant platforms for studying diseases and drug evaluation, replicating the native skin structures and functions more accurately than traditional 2D or simple 3D cultures. However, challenges remain in creating models suitable for microneedling applications and monitoring, as well as developing skin cancer models for analysis and targeted therapy. Here, we developed a human skin/skin cancer-on-a-chip platform within a microfluidic device using bioprinting/bioengineering techniques. The fabricated skin models include vascular, dermal, and epidermal layers, demonstrating increased functionalities and maturation of dermal (Collagen I & Fibronectin for 7 days) as well as epidermal (Filaggrin & Keratin 10, 14, and 19 at the air-liquid interface (ALI) for 21 days) layers. Histological analysis confirmed the formation of a differentiated epidermis and ridges at the dermal-epidermal junction in our model, closely resembling native skin tissue. Melanoma cells were embedded approximately 400 μm beneath the epidermis to simulate tumor invasion into the dermis. The platform was further used to test doxorubicin (DOX)-loaded gelatin methacryloyl (GelMA) microneedles (MNs) for localized transdermal drug delivery targeting melanoma. The DOX-loaded MNs penetrated uniformly to a depth of approximately 600 μm, effectively reaching the melanoma cells. Drug delivery via MNs demonstrated significantly higher efficiency than diffusion through media flow, confirming the practicality and robustness of the proposed model for future therapeutic applications.